Analisis Strategi Pemasaran Mengunakan Metode Quantitative Strategic Planning Matrik (QSPM) Studi Kasus : Borneo Project - Anas Mujahid; Murianai Emelda Isharyani; Dharma Widada (Jurnal Rekayasa Sistem Industri, 2018)
Borneo Project is a new business in the field of ordering services of various types of clothing. In doing its marketing strategy Borneo Project relies on marketing through friendship, word of mouth from one to another one and using social media as a marketing tool. This has not had a much positive effect on sales in Borneo Project. Therefore it is necessary to analyze the marketing strategy that can be applied in Borneo Project.Determining the strategy carried out in three stages: an input stage, matching stage, and the stage of the decision. The input stage is done by using Internal Factor Evaluation Matrix (IFE) and External Factor Evaluation Matrix (EFE). In the IFE matrix, obtained a total score of 2.407, while the EFE Matrix obtained score of 2.831. Based on internal and external factor analysis then matching phase with IE Matrix method and SWOT Matrix. The final stage was the decision stage used QSPM method. QSPM is used to evaluate alternative strategies obtained in the SWOT Matrix, then rank them. The first rank is the strategy of applying for credit funds, seeking investors or business joint venture partners and seeking financial assistance from corporate CSR with the acquisition of power score Pull of 5,824. Alternative strategies are prioritized to be applied is to ask a credit fund, seek a joint venture partner and investor or business and are looking for financial aid CSR.Keywords: Marketing Strategy, Borneo Project, QSPM